Nanomedicine for the prevention, treatment and imaging of atherosclerosis. - Psarros, C; Lee, R; Margaritis, M; Antoniades, C (2012)
Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in developed countries, with an increasing prevalence due to an aging population. The pathology underpinning CVD is atherosclerosis, a chronic inflammatory state involving the arterial wall. Accumulation of low density lipoprotein (LDL) laden macrophages in the arterial wall and their subsequent transformation into foam cells lead to atherosclerotic plaque formation. Progression of atherosclerotic lesions may gradually lead to plaque related complications and clinically manifest as acute vascular syndromes including acute myocardial or cerebral ischemia. Nanotechnology offers emerging therapeutic strategies, which may have advantage overclassical treatments for atherosclerosis. In this review, we present the potential applications of nanotechnology toward prevention, identification and treatment of atherosclerosis.